Deformation Consistency Analysis of Both the Door and Bpillar  During the Door Collision from the Side - WU Shi; ZHAO Hong-wei (Journal of Harbin University of Science and Technology)
In order to accurately study the consistency between the door and the Bpillar during the collision process and better analyze the influence of the deformation of the front and rear doors on the B column deformation during the side collision of the door Firstly, based on the vehicle side collision model information, the finite element model is solved by LSDYNA. Then the position of the corresponding position of the dummy on the Bpillar in the body side structure and the position of the left front door and the left rear door are selected to dynamically analyze the intrusion and intrusion speed of the Bpillar and front and rear doors. Finally, the energy changes during the deformation of the door and the deformation of the Bpillar are analyzed The simulation results show that in the process of side collision, the change trend of intrusion speed and intrusion amount of the door and the Bpillar is the same, the intrusion velocity shows a cosinetype change with time, and the intrusion amount shows a γtype change with time In the side process of the vehicle, the greater intrusion speed of the front and rear door intrusion , the greater influence on the Bpillar, which provides a basis for the optimization of the door structure and the improvement of the assembly quality of the door